Economic phenomena via mathematical modelling in maple system - Chvatalova, Zuzana; Simberova, Iveta (Business, Management and Economics Engineering, 2011)
Nowadays, economics utilizes more and more frequently quantitative methods. This is an important phenomenon in the process of education. The paper deals with application of the Maple system for on-line creation of mathematical models in economic sectors. Means of Maple represent an important challenge for application in practice or research – resolve specific problems, apply mathematical models in many science fields, create intelligent documents for the presentation of modelling and analyses with computations, visualizations, animations, simulations. The paper incorporates selected samples of models in Maple and indicates further fields of its practical using, e.g. for measurement of marketing activity effectiveness.